Prevalence and Knowledge of Hepatitis B Virus Infection among Pregnant Women in the Ningo-Prampram District, Ghana - Precious Kwablah Kwadzokpui; Elliot Elikplim Akorsu; Albert Abaka-Yawson; Solomon Sosu Quarshie; Stephen Adomako Amankwah; Philip Apraku Tawiah (International Journal of Hepatology)
Background. Hepatitis B virus (HBV) infection has been suggested to play a role in various adverse birth outcomes. The study determined the prevalence as well as knowledge of hepatitis B virus infection among pregnant women in the Ningo-Prampram District of the Greater Accra Region of Ghana. Materials and Methods. A cross-sectional study using simple random sampling technique was used to recruit 213 pregnant women receiving antenatal care in three different health facilities (Prampram Polyclinic (PPC), Dangme Community Hospital (DCH), and Old Ningo Health Center (ONHC)) in the Ningo-Prampram District of Ghana from November 2018 to January 2019. A semi-structured questionnaire was used to collect data which included participants’ HBsAg test results, sociodemographic and gynaecological characteristics, and their level of knowledge on HBV infection. Knowledge of the participants on HBV infection was classified as either excellent, good, or poor based on their cumulative percentage scores from the questionnaire according to Al Rubaish system of classification. Results. Overall low-intermediate prevalence of HBV infection was 3.3%; however, PPC recorded the highest prevalence of 4.0% while DCH and ONHC recorded 2.82% and 2.50%, respectively. Statistically significant association was observed between HBV infection and the health facility. Majority (77.40%) of the study participants had poor knowledge on HBV infection while only 14 (6.57%) had excellent knowledge on HBV. Regarding excellent knowledge, 8 (11.0%) among the participants were demonstrated by the majority of those who received antenatal care from DCH. Generally, knowledge on HBV and the infection was poor among the study participants. Knowledge on HBV infection was found to be associated with residential status (p=0.006), educational level (p<0.001), occupation (p<0.001), and gestational period (p<0.001). Participant’s knowledge was also significantly associated with the health facility (p=0.027). Conclusion. HBV infection among pregnant women is prevalent in the Ningo-Prampram District even though the prevalence is not very high. The majority of pregnant women in the Ningo-Prampram District inadequate knowledge on HBV infection and it mode of transmission. Intensive public health education on the HBV infection is required in the district to help prevent and manage future transmissions as well as inform the population about the negative side effects of the virus and the need to prevent it by way of vaccination.